2002
DOI: 10.1111/j.1749-6632.2002.tb04587.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization Studies of an Acoustically Excited Liquid Sheet

Abstract: The interaction between atomizing air and a liquid sheet initiates interfacial instabilities that develop into large amplitude waves, which ultimately promote liquid disintegration. However, to reduce atomizing airflow, the dynamic influence of the surrounding gas is not sufficient to affect the inner core of the liquid. In other words, the characteristic length scales of perturbation promoting break-up are small in comparison with the initial liquid momentum. Therefore, to enhance the disintegration process, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…It was observed that the interaction of the acoustic field with the sheet generates a sinuous wave riding on it. Flat liquids sheet having large aspect ratio sandwiched between two impinging air streams in the presence of acoustic excitation was studied by Sivadas & Heitor (2002) and Sivadas, Fernandes & Heitor (2003). Their result showed that the breakup of the liquid sheet gets enhanced and there is reduction in the breakup length of the sheet with acoustic excitation.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the interaction of the acoustic field with the sheet generates a sinuous wave riding on it. Flat liquids sheet having large aspect ratio sandwiched between two impinging air streams in the presence of acoustic excitation was studied by Sivadas & Heitor (2002) and Sivadas, Fernandes & Heitor (2003). Their result showed that the breakup of the liquid sheet gets enhanced and there is reduction in the breakup length of the sheet with acoustic excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic oscillations affect the spray by forming large-scale vortical structures which entrains droplets, [3,4] alters velocity field [4] and can increase evaporation rates, [4] thereby decreasing droplet size [5,6], resulting in finer atomization [7] and enhancing combustion process [8]. These oscillations improve spray development and patternation by changing liquid disintegration characteristics [9,10]. Studies performed on flat liquid sheets showed that acoustic excitation results in structurally different liquid disintegration characteristics as compared to unexcited flows [10].…”
Section: Introductionmentioning
confidence: 99%
“…These oscillations improve spray development and patternation by changing liquid disintegration characteristics [9,10]. Studies performed on flat liquid sheets showed that acoustic excitation results in structurally different liquid disintegration characteristics as compared to unexcited flows [10]. In the presence of acoustic oscillations, the interfacial wave development on the liquid sheet reduces surface tension dominated instability [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations